SOME CONCEPTUAL IDEAS OF TRAINING ORGANIZATION IN NONSTATE ECONOMIC UNIVERSITY - Valery Nikolayevich Kharchenko (Advanced Engineering Research, 2013)
A whole complex of factors that may facilitate the effective training organization in the nonstate economic university is proved. In this case, each of the mentioned factors is regarded as a conceptual idea developing in the accordance with the common concept of the nonstate educational institution of the higher vocational education. A program assessment mechanism for the educational process quality and the final quality of the graduate education is offered. The basic content and the implementation phases of the author’s model aimed at the quality assurance of the  university educational and scientific activities results are stated. An original information card makeup for a student of Rostov Institute of Protection of the Business-man specialized in marketing is offered, its content is described. The internal audit planning and performance are stated, the objective fulfillment mechanism for the audit conducted on the process control basic parameters of the student professional competence formation is offered. The evaluation criteria and subcriteria of the proficiency level for the students-economists are mentioned.